Procedural reform at the Arctic Council: the amended 2015 Observer Manual. (8th April 2016) - Knecht, Sebastian
ABSTRACT: This note studies the addendum to the Arctic Council (AC)'s 2013 Observer Manual adopted at the Senior Arctic Officials' (SAO) meeting in Anchorage, Alaska, in October 2015. The amendment means another essential step to systematise further and improve the council's working relations with currently 32 entities that hold observer status in the forum. Compared to the initial manual that sketched out the role observers should play in the council's subsidiary bodies, the latest revisions delineate a framework for enhancing observer participation and commitment in working group, task force and expert group meetings. After reviewing the content and practical implications of the addendum in the context of larger reform efforts to adapt the council to the age of a global(ising) Arctic, the article further discusses a number of signals the Anchorage decision sends to observers. These comprise the council's willingness and ability to quick, unified and purposeful action towards institutional adaptation and procedural reform as considered necessary to address organisational deficiencies, strengthened top-down steering of the reform processes by SAOs as related to the work conducted in subsidiary bodies and the overall functioning of the council, and higher expectations on observers to contribute to the AC system and deliver on the new provisions.